Chaetophractus tarijensis (Xenarthra, Dasypodidae) : ¿Un endemismo del valle de Tarija (Bolivia)? Implicancias paleobiogeográficas - Rodriguez Bualó, Santiago (2014)
Chaetophractus tarijensis (Ameghino) is a dasypodid restricted to the Pleistocene of the Tarija Valley (Bolivia). In this contribution we study the type specimen of C. tarijensis and referred specimens to this species, and establish comparisons with extant Dasypodidae Euphractinae. The analysis of the present study reveal that the characters used by Florentino Ameghino (e.g. the underdevelopment of the angular portion of the ramus of the mandible and the cylindrical shape of the last molariform) do not allow the differentiation with Chaetopractus (Desmarest). Also, a principal components analysis was performed with cranial measurements. All these evidence support the hypothesis that C. tarijensis is a synonym of C. villosus. From a paleobiogeographic point of view, these results are important because it indicates that C. tarijensis is not one of the few supposedly endemic species of the of the Tarija Valley.